Ribose Alters the Photochemical Properties of the Nucleobase in Thionated Nucleosides - Janicki, Mikołaj J; Kufner, Corinna L; Todd, Zoe R; Kim, Seohyun C; O'Flaherty, Derek K; Szostak, Jack W; Šponer, Jiří; Góra, Robert W; Sasselov, Dimitar D; Szabla, Rafał (The journal of physical chemistry letters, 2021)
Substitution of exocyclic oxygen with sulfur was shown to substantially influence the properties of RNA/DNA bases, which are crucial for prebiotic chemistry and photodynamic therapies. Upon UV irradiation, thionucleobases were shown to efficiently populate triplet excited states and can be involved in characteristic photochemistry or generation of singlet oxygen. Here, we show that the photochemistry of a thionucleobase can be considerably modified in a nucleoside, that is, by the presence of ribose. Our transient absorption spectroscopy experiments demonstrate that thiocytosine exhibits 5 times longer excited-state lifetime and different excited-state absorption features than thiocytidine. On the basis of accurate quantum chemical simulations, we assign these differences to the dominant population of a shorter-lived triplet nπ* state in the nucleoside and longer-lived triplet ππ* states in the nucleobase. This explains the distinctive photoanomerziation of thiocytidine and indicates that the nucleoside will be a less efficient phototherapeutic agent with regard to singlet oxygen generation.
Keywords: Photochemical Processes; Nucleosides; síra; Ribose; fotochemické procesy; ribosa; nukleosidy; Sulfur